Irrational Diversification: An Examination of Individual Portfolio Choice - Baltussen, Guido; Post, Gerrit T. (Journal of Financial and Quantitative Analysis, 2011)
Abstract We study individual portfolio choice in a laboratory experiment and find strong evidence for heuristic behavior. The subjects tend to focus on the marginal distribution of an asset, while largely ignoring its diversification benefits. They follow a conditional 1/ n diversification heuristic as they exclude the assets with an “unattractive” marginal distribution and divide the available funds equally between the remaining “attractive” assets. This strategy is applied even if it leads to allocations that are dominated in terms of first-order stochastic dominance and is clearly irrational. In line with these findings, we find that framing and problem presentation have substantial influence on portfolio decisions.